The Role of Adaptive Leadership in Enhancing Generation Z Employee Performance within Technology Startups - Apriyanto, Afdal; Maria, Yanti (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
Technology startup development quickly has fueled extreme need for adaptive leadership to succeed in a state of uncertainty and deliver to the expectations of the new generation of employees. This study aims to examine the contribution of adaptive leadership towards enhanced Generation Z employees' performance in Indonesia's technology startups. A researcher used a quantitative explanatory design based on 182 Generation Z workers in Greater Jakarta technology startups. Data were collected using an online five-point Likert-scale questionnaire and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The findings are that adaptive leadership has a significant positive effect on employee performance both directly and indirectly via employee engagement. The path coefficient (β = 0.72) indicates the very strong effect of adaptive leadership on Generation Z performance, with 64% variance explained by the model. Theoretically, this study advances Complexity Leadership Theory application to the field of digital workforce. In terms of practice, it provides startup leaders with a means to build adaptive, collaborative, and flexible leadership styles. The study thus contributes theoretically to research on adaptive leadership and practical solutions to optimizing the performance of young employees in technology settings.